Mujeres desde el Vaticano II : memoria y esperanza - Martínez Cano, Silvia (Aletheia (Estella, Spain), 2014)
Women from Vatican II is a multi-path memories and looks to the challenges of the event which marked the Council. Read from the experiences of various characters who lived through the historical moment, goes into a joint reflection on the joys of the changes that Vatican II began.